Synchronous Haematogenous Colonic Metastasis from a Primary Renal Cell Carcinoma: An Unusual Cause of Colonic Haemorrhage: (Case Report) - Abu-Khalaf, Mahmoud; Khatib, M. Amer Khatib; Samara, Osama; Fayyad, Luma (Jordan Medical Journal, 2016)
Background: Renal cell carcinoma (RCC) represent 2-3% of all malignant tumors in adults. Clear cell carcinoma is the most frequent histological type, and 25-30% of renal carcinoma have metastasis at the time of diagnosis. RCC very rarely metastasize to the colon. The objective of the present study is to report synchronous haematogenous solitary colonic metastasis that presented as severe recurrent lower gastrointestinal haemorrhage which required right hemicoloectomy and right nephrectomy plus chemotherapy.Clinical Case: We report the case of a 46-year old male patient who presented with multiple episodes of severe haemotochezia and anemia. He had a right flank mass. CT scan of the abdomen showed a large right kidney mass together with a lesion in the ascending colon, not connected to the renal mass. It also showed hepatic metastasis, lung metastasis and ascites. Colonoscopy revealed an ascending colonic mass. The patient was managed by right nephrectomy and right hemicolectomy. The pathology report of the colonic mass showed clear cell carcinoma with involvement of the colon from serosa to mucosa. It indicated the presence of haematogenous spread of the RCC as the mechanism of metastasis. The colonic haemorrhage did not recur. the patient survived close to a year after surgery.Conclusion: RCC metastasis to the colon is very rare and can be synchronous with the primary renal tumor and can be metachronous after nephrectomy. Also, it can be the result of direct invasion, haematogenous spread or after local recurrence following nephrectomy. Metastatic RCC requires surgery, immunotherapy, tyrosine kinase inhibitors, and mammalian target rapamycin inhibitors. Surgery is the first step for disease control and control bleeding from colonic metastasis. Metastectomy is indicated in localized disease and when surgically accessible.